Development of Interactive Multimedia Based on Problem-Based Learning to Improve Learning Outcomes of Light Properties Material - Selviana, Selviana; Andriani, Aldina Eka (Jurnal Pijar Mipa, 2025)
The use of technology in science learning media is not optimal, causing low learning outcomes for students. This study aimed to develop a design and test the feasibility and effectiveness of interactive multimedia based on Problem-Based Learning to improve the learning outcomes of fifth-grade students of SDN Pesantren Semarang City. The type of research is Research and Development (R&D) using the Borg and Gall model. The research subjects were 26 fifth-grade students of SDN Pesantren. Data collection techniques using non-test techniques (observation, interviews, questionnaires, and documentation) and test techniques (pre-test and post-test). Data analysis techniques used normality test, t-test, and N-Gain test. The results showed that the design of Problem-Based Learning-based interactive multimedia development using the Canva application contains the main page, main menu, instructions for use, concept map, Problem-Based Learning-based learning materials, virtual laboratories (Dynamic Labs), learning videos, interactive quizzes (Genially), and developer profiles; the feasibility of Problem-Based Learning-based interactive multimedia from material experts 93.75% very feasible criteria and media experts 92.18% very feasible criteria. The results of the teacher response questionnaire are 100% very feasible criteria and 96.80% student response with very feasible criteria; the effectiveness of interactive multimedia based on Problem-Based Learning is shown from the increase in pre-test and post-test scores by 33.65, paired sample t-test results show the significance value (2-tailed) is <0.001 which based on the criteria the value is below 0.05, and the N-gain test results are 0.6913 medium criteria. This study concludes that interactive multimedia based on Problem-Based Learning was successfully developed, very feasible, and effective in improving the learning outcomes of the properties of light material for fifth-grade students of SDN Pesantren Semarang City.